Carbon Footprint of Elephant Mammal Management in Taman Margasatwa Ragunan Using Life Cycle Assessment Approach - Ninin Gusdini; Siti Aminatu Zuhria (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Tourism is the second largest contributor to Indonesia's foreign exchange. In addition, tourism can be a leverage factor for other developments, especially in the socio-economic field. nHowever, this development can have an impact on environmental quality such as climate chage. Jakarta as an urban area has many tourism potentials, one of which is Taman Margasatwa Ragunan (TMR). The development of urban tourism has become a new trend in the community because the distance traveled is relatively closer and the cost is relatively cheaper. In its development, urban tourism needs to be controlled and well designed in order to be sustainable. This study aims to identify the impacts that may arise and calculate the carbon emissions generated from elephant management. Elephants are taken as the object of study because among the existing animals, elephants are the animals with the most food consumption and produce the most carbon emissions. The method used to calculate environmental impacts is life cycle assessment (LCA). The scope taken in this study is gate to gate, so that the impacts taken into account are those that occur in the process of raising elephants. The research began with observation of Ragunan Wildlife Park to identify input-process-output components in elephant management. The results showed that the carbon footprint value of elephant mammal management in TMR was 4.62 kg CO2eq/elephant. The hotspot GHG emission-contributing sector is elephant feed in the form of elephant grass